2015
DOI: 10.4238/2015.october.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Ebp1 and p53 protein expression in cervical cancer

Abstract: ABSTRACT. In this study, the ErbB3-binding protein (Ebp1) and p53 protein expression in cervical cancer tissues, and its significance in the prognosis of the disease was investigated. Ebp1 and p53 protein expression was detected by immunohistochemical analysis in cervical cancer tissues (N = 60) and normal tissues adjacent to the cancer tissues (N = 60). The rates of positive Ebp1 and p53 protein expression were 35.0 and 60.0%, respectively. Ebp1 and p53 were overexpressed in cervical cancer tissues, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…EBP1 was originally identified as an ErbB3 binding protein which was considered as an oncogene or tumor suppressor in different circumstances (3841) and has prognostic significance in a panel of cancers such as cervical (7, 42), pancreatic (6), hepatocellular (43), brain (44) and other tumors. Recent study has clarified that EBP1 possesses two isoforms, the longer form P48 and the shorter form P42, which distinctively regulate cell survival and differentiation (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBP1 was originally identified as an ErbB3 binding protein which was considered as an oncogene or tumor suppressor in different circumstances (3841) and has prognostic significance in a panel of cancers such as cervical (7, 42), pancreatic (6), hepatocellular (43), brain (44) and other tumors. Recent study has clarified that EBP1 possesses two isoforms, the longer form P48 and the shorter form P42, which distinctively regulate cell survival and differentiation (5).…”
Section: Discussionmentioning
confidence: 99%
“…The predominant P48 isoform can promote cell proliferation, differentiation or survival including cancer cells (4, 6), and localizes to both cytoplasm and nucleus (5). Moreover, correlation of high expression level of P48 with poor clinical outcomes in pancreatic ductal adenocarcinoma (6), brain tumor (4), cervical (7) and prostate cancer patients (8) suggests P48 is closely related with cancer progression. In contrast, the P42 isoform which lacks the N-terminal 54 amino acids is considered to be a potent tumor suppressor because of its growth inhibitory function (3, 5, 9).…”
Section: Introductionmentioning
confidence: 99%
“…The level of p53 was also associated with lymph node metastasis (p < 0.05) [32]. A study in 60 cervical cancer samples and 60 controls also showed higher p53 levels in the cervical cancer samples than the normal samples (p < 0.05), and the elevated p53 level was also associated with lymph node metastasis (p < 0.05) [33]. This identifies p53 as a robust prognostic biomarker in cervical cancer, even though its regulatory mechanism needs to be elucidated further.…”
Section: Expression Profiles Of Biomarkersmentioning
confidence: 94%
“…P53 protein expression in cervical cancer tissue samples was not correlated with patient age, grade and stage of tumors (p > 0.05). An earlier report on cervical cancer stated that the protein expression level of p53 in the tumor tissues was significantly higher compared to that of the normal adjacent tissue [35]. Moreover, the same study reported that p53 protein expression in cervical cancer tissue samples was not correlated with the patient age, tumor size, or family history [35].…”
Section: Discussionmentioning
confidence: 94%